The role of acute in‐patient rehabilitation on short‐term outcomes after liver transplantation: A systematic review of the literature and expert panel recommendations. Issue 9 (18th September 2022) - Mina, Daniel Santa; Tandon, Puneeta; Kow, Alfred Wei Chieh; Chan, Albert; Edbrooke, Lara; Raptis, Dimitri Aristotle; Spiro, Michael; Selzner, Nazia; Denehy, Linda; ,
Abstract: Background: The indication and surgical complexity of orthotopic liver transplantation underscore the need for strategies to optimize the recovery for transplant recipients. We conducted a systematic review aimed at identifying, evaluating, and synthesizing the evidence examining the effect of in‐patient rehabilitation for liver transplant recipients and provide related practice recommendations. Methods: Health research databases were systematically reviewed for studies that included adults who received liver transplantation and participated in acute, post‐transplant rehabilitation. Postoperative morbidity, mortality, length of hospital stay, length of intensive care unit stay, and other markers of surgical recovery were extracted. Practice recommendations are provided by an international panel using GRADE. Results: Twelve studies were included in the review (including 3901 participants). Rehabilitation interventions varied widely in design and composition; however, details regarding intervention delivery were poorly described in general. The quality of evidence was rated as very low largely owing to "very serious" imprecision, poor reporting, and limited data from comparative studies. Overall, the studies suggest that in‐patient rehabilitation for recipients of liver transplantation is safe, tolerable, and feasible, and may benefit functional outcomes. Conclusion: Two practice recommendations related to in‐patient rehabilitation following LT were yielded from this review: (1) it is safe, tolerable, and feasible; and (2) it improves postoperative functional outcomes. Each of the recommendations are weak and supported by low quality of evidence. No recommendation could be made related to benefits or harms for clinical, physiological, and other outcomes. Adequately powered and high quality randomized controlled trials are urgently needed in this area.